ASSOCIATION OF SCAR TENDERNESS AND OTHER CLINICAL SIGNS WITH SCAR COMPLICATIONS IN PATIENTS UNDERGOING THE TRIAL OF LABOR AFTER CESAREAN SECTION - Liaqat, Nazia; Qazi, Qudsia (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine association between scar tenderness and other clinical signs of scar complications in patients undergoing a trial of labor after cesarean section. Methodology: This case-control study was conducted in the Department of Obstetrics and Gynaecology, Lady Reading Hospital, Peshawar from June 2017 to June 2019. Patients with scar complications at repeat emergency cesarean section, after a failed trial of labor, were taken as cases. Controls were patients, who were found to have intact scars at repeating emergency cesarean delivery after trial of labor. Cases were compared with controls for the presence of scar tenderness, maternal tachycardia, and Cardiotocography (CTG) abnormalities. Data were analyzed using SPSS Version 23.0. Results: Sixty-six women were enrolled, with an age range of 21-40 years with a mean age of 27±43.42 years for cases, and 28.66±4.85 for controls. The association of scar tenderness alone (p=0.2), maternal unexplained tachycardia alone (p=0.886), and abnormal CTG alone (p=0.44) with scar complications were not significant. A significant association was observed between a combination of scar tenderness, abnormal CTG, and maternal tachycardia with scar complications (p=0.006, aOR=21.33, CI:2.37-19.20). Conclusion: A combination of clinical signs including scar tenderness and unexplained maternal tachycardia as well as abnormal CTG serve as a valid indicator of impending scar complications and should be included in the monitoring of women undergoing the trial of labor after a previous cesarean.